How can emerging technology remedy the deficiency in robust enforcement mechanisms for digital copyright infringement within the South African music industry? - Mushati, Julita (Department of Commercial Law, 2026)
This dissertation examines the deficiency in robust enforcement mechanisms for digital copyright infringement within the South African music industry, which constant technology developments have worsened. The emergence of technology has been a dual-edged sword for the music industry. While it empowers musicians to reach vast consumers, it simultaneously simplifies and accelerates unwarranted copying, access, and reproduction of copyrighted material. Consequently, protecting intellectual property rights has become strenuous due to the rapid increase of file-sharing systems, therefore, prompting a dire need for modernised solutions. The principal purpose of this research is to explore how emerging technologies can assist in reinforcing enforcement mechanisms and analyse the deficiencies in the South African music industry context. This study utilises a desk research method examining emerging technologies and their association with the enforcement of copyrights in the music industry. Technologies such as Digital audio watermarking, Blockchain technology, artificial intelligence, quantum computing, digital audio fingerprinting, and machine learning will be examined in this paper, and how these emerging technologies can potentially establish robust enforcement mechanisms. In particular, the findings of this research reveal the dual role of technology that enables digital copyright infringement, which presents a substantial threat to the protection of copyright, however, emerging technology can be tactically employed to address the enforcement challenges, and the need for Copyright laws to be at par with technological advancements. This dissertation provides informative and valuable awareness of the relationship between merging technology and enforcement mechanisms within the context of the South African music industry and how this relationship can foster an environment that upholds copyright works and affords musicians the recognition and financial incentive they deserve.